The nursing care in the spiritual dimension: undergraduates’ experience - Souza, Janei Rabello de; Maftum, Mariluci Alves; Mazza, Verônica de Azevedo (Online Brazilian Journal of Nursing, 2009)
Exploratory descriptive research objectifying: know how nursing undergraduates experience care in the spiritual dimension. Ten students participated and data were collected through a semi-structured interview and organized in the following categories. The study aimed to reflect upon nursing education towards the related contents of spiritual care in nursing practice. Apprehending how their beliefs have supported them to care in the spiritual realm. They reported the difficulties in apprehending a person’s spiritual dimension but they acknowledge its significance in caring. Unknowing the subject makes them insecure to deliver such caring.